Managing the Jakarta Megalopolitan: Quo Vadis? - Maksum, Irfan Ridwan (Makara Human Behavior Studies in Asia, 2009)
The choice of institutional development for Jakarta as Indonesian capital city can be the barometer of equity and fairness as value to whole developing nation, especially for urban development in Indonesia. If megalopolis concept proposed by Sutiyoso received without reverse, then we have disease to the equity and fairness values as a nation state. Megalopolis is a city characterized by: (1) huge population and density; (2) national and international networking scale; (3) huge integrated spatial. The problematic situation of urban development in Jakarta is urgent, but it is un-fair and unequal if development of other cities in Indonesia is abandoned. The choice to develop megalopolis is still unclear.